An Analysis of Linguistic Features of Evaluative Stance Found in Research Articles’ Introduction - Mubarok, Tyas Alhim (BRILIANT: Jurnal Riset dan Konseptual, 2021)
This study aims to identify the use of linguistic feature of evaluative stance found in research articles’ introduction. There are certain linguistic features that indicate evaluative stance. That is how writers position themselves in their writing. By knowing those items, it can be known how the authors provide words usage to produce effective meaning. This study focuses on the use of epistemic modality, extraposed ‘ít’, communication verb, and personal pronoun. The method of this study applied both quantitative and qualitative research method. The data were gained from research article written in English limited in introduction section that taken from international journal of Journal of Development Research. The result showed that all of type of linguistic feature of evaluative stance found in introduction of articles. The most frequent used is personal pronoun. Then followed by epistemic modality, extraposed ‘it’ and the lowest is communication verb. This study is expected to provide more insightful reference in the field of linguistics study.